The Role of Physical Culture in Human Life (Eurasian Scientific Herald, 2021)
The work examines the importance of physical culture and physical education in human life. Lack of human physical activity is recognized as a global problem of the modern world, as it leads to malfunctions in the work of all systems and the body as a whole, contributing to the occurrence of various diseases.